Molecular Identification Of Human Papilloma Virus Genotypes In Patients With Cervical Cancer - Piña Napal, Juan Carlos; Crespo Campos, Gustavo; Fando Calzado, Rafael; Valdés Silva, Yaimara (Revista Cubana de Investigaciones Biomédicas, 2019)
Background: The principal cause of cervical cancer is human papillomavirus. In Camaguey population, molecular study about human papillomavirus does not exist. The Polimerase Chain Reaction is a molecular procedure often used for medical diagnostic; it allow to confirm the human papillomavirus DNA in the total DNA purified of cervical cancer patients sample. Objetive: The first time demonstration the human papillomavirus circulating in the cancer cervical patients of Camaguey population, Cuban. Methods: The analytic study was carried out with 22 patients of the pathology consult of Genecology hospital of Camaguey. The identification and characterization of human papillomavirus genotype was carried out through restriction fragment lenght polymorphic procedure. Results: The mean age was 52.3 years and the more frequency was the 50-59 age group in 50% of the women. Were studied by cytology only 10 women and the false negative of the cytology was of 80%. The 63.3 percent of patients showed exophytic lesion, 4.5 percent endophytic lesion and 3.8 percent another lesion. Were studied by cytology only 10 women of the total participants and the false negatives were of 80%. The 16 and 31 was the circulation genotypes in the Camaguey population and the 16 genotype was the most frequently. Conclusions: This is the first report of molecular study of human papillomavirus in cervical cancer patients on Camaguey, Cuban. Present research and the other research of Cuban authors is an important contribution to therapeutic and prevent vaccine more effective in the solution anticipate for the cervical cancer in Cuban.